After the Storm Has Passed: Translating Crisis Experience into Useful Knowledge - Lee, Gwendolyn K.; Lampel, Joseph; Shapira, Zur (Organization Science, 2020)
This virtual special issue (VSI) collects together 19 papers published in Organization Science that explore how organizations learn from crises. The objective is to discuss insights that can help us understand the COVID-19 pandemic crisis, implications that existing research carries for organizations’ abilities to keep hard-earned lessons after the storm passes, and opportunities that the current phenomenon offers for future inquiry in this domain. Organizations, large and small, in scores of countries, have suspended normal operations. To survive, many organizations have adapted by shifting almost all human-to-human interactions online while facing an ethical dilemma and a tense tradeoff between public health and economic well-being. We take stock of the research on organizational learning from crises, summarize useful knowledge for managing the current crisis, and provide directions for future research.